The role of S100a4 (Mts1) in Apc- and Smad4-driven tumour onset and progression. (November 2016) - Atlasi, Yaser; Noori, Rubina; Marolin, Ivana; Franken, Patrick; Brandao, Joana; Biermann, Katharina; Collini, Paola; Grigorian, Mariam; Lukanidin, Eugene; Ambartsumian, Noona; Fodde, Riccardo
Abstract: Introduction: S100a4 is a calcium-binding protein belonging to the family of S100-proteins, highly expressed in different stromal cell types. S100A4 has been reported as a prognostic marker in colorectal cancer in association with tumour progression and metastasis. Methods: In this study, we analysed the in vivo role of S100a4 in intestinal tumour initiation and progression using different transgenic and knockout mouse models. Results: We found that genetic ablation or overexpression of S100a4 in both Apc- and Smad4-mutant mice do not affect tumour initiation in the intestinal tract. In contrast, S100a4 epithelial overexpression in Apc 1638N/+ /KRAS V12G mice increases the dissemination of intestinal tumour cells to the liver, in agreement with its role in tumour metastasis. Moreover, we report a novel role for S100a4 in desmoid formation where S100a4 deficiency results in a significant reduction of the tumour burden characteristic of the Apc 1638N model. In agreement with these results, S100a4 appears to be co-expressed together with mesenchymal stem cell (MSC) markers in desmoid tumours from Apc 1638N/+ mice, as well as from sporadic and hereditary human desmoids. Conclusion: Our data provide the first report on the in vivo role of S100a4 in intestinal tumourigenesis and describe a new role for S100a4 in the aetiology of desmoids formation. Highlights: Genetic ablation or overexpression of S100a4 in both Apc- and Smad4 -mutant mice do not affect intestinal tumour initiation. S100a4 overexpression in Apc1638N /+/ KRAS V12G mice increases the dissemination of intestinal tumour cells to the liver. S100a4 deficiency results in a reduction of desmoids suggesting a novel role for S100a4 in desmoid formation. S100a4 is co-expressed together with mesenchymal stem cell (MSC) markers in desmoid tumours.